MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM BAGI ANAK YATIM PIATU DALAM TINJAUAN SOSIAL - Rustina, Rustina (Musawa: Journal for Gender Studies, 2020)
In general, social conditions affect children's activities and motivation in studying. Related to the issue, the discussion in this paper sees that children are a gift from Allah SWT that is always expected by every appropriate guidance with social development both in society and in family. However, not everyone can look after their children properly according to what is ordered by Allah SWT through religious teachings. For various causes and reasons, parents do not pay attention to the religious education of their children. In the end, the negative impact will be strongly felt by parents, especially for the children themselves. In order to forming religious education in children in these conditions, the community involvement is needed as a social element. The main factors influencing learning motivation of orphans are the factor from within (internal) and from outside (external). But the most fundamental is child psychology which is something that is not separated from human life itself, so that these condition of social differences become the most influencing factor for the orphans and neglected children in doing their learning activities. Thus, the conclusion is that social conditions are something highly determines the learning motivation that can change the level of self-confidence for the orphans. Hence, the cooperation of the government and observers of society condition must keep on trying to provide the supports in the form of attention, affection, guidance and also try to develop abilities and shape characters of the children, which are not only their intellectual capability but also their moral through various forms of religious education.